Teksty ze wsi Darwinieki oraz z Iłukszty na Łotwie z komentarzem językowym - Małgorzata Maria Ostrówka (Acta Baltico-Slavica, 2015)
Texts from the villages Darvinieki and Iłukszta in Latvia with linguistic comments The study contains dialect texts recorded in the village Darvinieki in the 1960s by Józefa Parszuta (a researcher of the Polish language who was born in Latvia) and texts recorded by the author in Iłukszta in 2001. The texts are preceded with a linguistic comment including a description of the most important phonetic, morphological and syntactic features which are characteristic of the Polish north borderland dialect.